Clinical Characteristics, risk factors and outcome in patients with in tracerebral haemorrhage - GJorcheva, Irena; Arsovska, Anita; Mitrevska Velkova Jasmina; Babunovska Marija; Stojchev, Sasho; Kuzmanovski Igor; Cherpeganova Changovska Tatjana; Isjanovski, Igor (Leage against epilepsy of Macedonia, 2015)
AbstractIntracerebral haemorrhage is a meaningful factors in the neurological praxis, as an urgent condition that requires timely detection and treatment with the purpose of improving trhe outcome. the aim of the study is to examine the clinical characteristics, risk factors and the outcome in patients with intacerebral haemorrhage. At the Department of urgent neurology of the University clinic of neurology in Skopje, Macedonia, a retrospective study was performed, with which 177 patients with intracerebralk heamorrhage, hospitalized at th University clinic of neurology within a two year period, are encompassed. the Main characteristics of the clinical features, risk factors, intrahospital complications and patient outcome werw researched. The results point to a nesessity of increased control of the risk factors with the patients, the effect of witch would be subject to futher studies.
Keywords: intracerebral hemorrhage; neurological deficit; complications; outcome; prevention